Primary Wound Closure Versus Delayed Primary Wound Closure in Complicated Appendicitis in Tikrit Teaching Hospital - Khazaal, Ahmed S; Habash, Mohammed M; Sarhan, Hamid H; Rasheed, Qusay S (Diyala Journal of Medicine, 2019)
Background: Two methods are used routinely for wound management following an appendectomy: delayed primary closure, which involves packing an open wound for 4-5 days followed by wound closure, and primary closure, which means closing the wound at the time of surgery. Primary closure has the potential benefit of rapid wound healing associated with the elimination of painful and time-consuming dressing, as well as a reduction in overall hospital costs. Objective: To compare the incidence of wound infection after primary wound closure and delayed primary closure in patients with complicated appendicitis. Patients and Methods: A total of 78 patients with complicated appendicitis (gangrenous, perforated, and abscess) admitted to surgical wards in Tikrit Teaching Hospital for a period of 12 months (January 2013 to January 2014). Males were 45 and females were 33, their ages ranged from 17-55 years were included in the study. The patients were adult males and non-pregnant adult females whom underwent appendectomy for complicated appendicitis. Results: Age and gender were not significant factors affecting wound closure type (p=0.772 and p=0.942 respectively). The mean period of symptoms duration in patients with delayed primary closure was significantly (p=0.037) longer (5.9±3.11 days), than that with primary closure (2.81±2.07 days). Duration of surgery was significantly (p=0.021) longer (37.98±6.7 minutes) for delayed primary closure, than for primary closure (22.71±8.11 minutes). The mean duration of stay per hospital was significantly (p=0.030) shorter (6.84±1.71 days) for delayed primary closure than for primary closure (8.7±0.94 days). Conclusion: A better overall results related to the strategy of delayed primary closure despite the relative longer time of surgery and greater efforts done by the surgeon. This will give benefits to both the patient and surgeon.